A novel optimal frequency control strategy for an isolated wind–diesel hybrid system with energy storage devices. Issue 6 (December 2016) - Kouba, Nour EL Yakine; Menaa, Mohamed; Hasni, Mourad; Boudour, Mohamed
This article presents the design of a new effective control strategy to enhance frequency stability of an isolated micro-grid-based wind–diesel hybrid system. The suggested control methodology involves load frequency control coordinated with battery energy storage systems. A recently developed meta-heuristic algorithm called multi-verse optimizer was applied to design an intelligent load frequency control scheme in the aim to handle the frequency fluctuation due to load changes and wind farm integration. The multi-verse optimizer algorithm was used to optimize the proportional–integral–derivative controller parameters for the load frequency control loop. The proposed controller was coordinated with two different kinds of storage system, which are redox flow batteries and electric vehicles. To demonstrate the effectiveness of the proposed control strategy, the simulation was performed under step load changes and then was extended with doubly-fed induction generator wind farm integration. Furthermore, to show the potential of multi-verse optimizer algorithm, a comparative study was done with other approaches available in the literature. In addition, robustness analysis was carried out. The obtained simulation results show that the proposed strategy is a very effective means for providing robust load frequency control controller and to avoid hybrid system instability. Furthermore, the system frequency can be improved using an optimal power management of the stored energy in both redox flow batteries and electric vehicles to compensate the load frequency control capability of the diesel groups, which allow to the possibility of integration of a large penetration of wind farms. In summary, the proposed control strategy may be helpful to identify the needed load frequency control capacity in the presence of dispersed generation's units.